A Influência do brincar tradicional para a educação ambiental no ensino de ciências - Carvalho, Marcio Aparecido de (2015)
This study examined the influence of traditional games in environmental education in science education, and aimed to study whether the traditional games are currently practiced by children. Our hypothesis is that children are currently influenced by modern technology and games, and that culture of traditional games is being lost with time. Structured interviews were conducted with children, formal education students (group 1) and adults (group 2) to find out if the games that adults knew and practiced in their infancy are still known and practiced by children today. Group 1 was composed of children aged 11 to 13 years and 2 adults per group 35-50 years both the city of Itapevi, SP. The results showed that children know a considerable part of traditional games, but compared to adults found that some traditional games are totally unknown to the kids today. It was also clear that children today spend much of their time inside their homes, either watching TV or playing alone. This shows that traditional games are no longer being practiced by current generations, and that the roles of socialization of traditional games are losing ground in our society.